Oxygen-deficient (Nd0.4Sr0.6)2Ni0.8M0.2O4-δ nickelates as oxygen electrode materials for SOFC/SOEC - Yaremchenko, Aleksey (2019)
Perovskite-related Ln2NiO4+δ (Ln = La, Pr, Nd) nickelates with layered Ruddlesden-Popper combine redox stability with noticeable oxygen stoichiometry changes, yielding enhanced mixed transport and electrocatalytic properties. These unique features are promising for applications as oxygen electrodes with good electrochemical performance in reversible SOFC/SOEC (solid oxide fuel/electrolysis cell) systems. To date, most efforts were focused on oxygen-hyperstoichiometric Ln2NiO4+δ-based phases, whereas nickelates with oxygen-deficient lattice remain poorly explored. Recent studies demonstrated that the highest electrical conductivity in (Ln2-xSrx)2NiO4±δ series at elevated temperatures is observed for the compositions containing ~ 60 at.% of strontium in A sublattice [1,2]. The present work was focused on the characterization of (Nd0.4Sr0.6)2Ni0.8M0.2O4-δ (M = Ni, Co, Fe) nickelates for the possible use as materials for reversible oxygen electrodes. The ceramic materials were prepared by Pechini method with repeated annealings at 650-1200°C and sintered at 1250-1300°C for 5 h under oxygen atmosphere. Variable-temperature XRD studies confirmed that all studied compositions retain tetragonal K2NiF4-type structure in the temperature range 25-900°C. The results of thermogravimetric analysis showed that the prepared nickelates has oxygen-deficient lattice under oxidizing conditions at temperatures above 700°C. Partial substitution of nickel by cobalt or iron results in a decrease of p-type electronic conductivity and the concentration of oxygen vacancies in the lattice, but also suppresses dimensional changes associated with microcracking effects (due to anisotropic thermal expansion of tetragonal lattice). Electrochemical performance of porous (Nd0.4Sr0.6)2Ni0.8M0.2O4-δ electrodes in contact with Ce0.9Gd0.1O2-δ solid electrolyte was evaluated at 600-800°C employing electrochemical impedance spectroscopy and steady-state polarization (anodic and cathodic) measurements.